Analisis Faktor-Faktor yang Mempengaruhi Ketidakpatuhan Wajib Pajak yang Terdaftar Pada KPP Pratama Sukoharjo - Retyowati, Fitriana Dikky; , Drs. Muhammad Abdul Aris, M.Si (2016)
This study aims to determine the effect perception tax equity system, social norms,moral norms, subjective norms, the risk pf detection, the magnitude of the sanctions, religiosity, and intention to behave disobeying noncompliance with the theory of planned behavior theory. The population in this study covers all individual taxpayers listed on STO Sukoharjo until 2015. The sampling technique is incindental sampling. Data isobtained by distributing questionnaires to129 respondents. Of the 129 respondents, 100 questionnaires can be processed. Data analysis is used in this research is multiple is multiple linear regression analysis. The result of this study indicate the perception tax equity system, social norms, moral norms, subjective norms, the risk of detection, the magnitude of sanctions, religiosity, and intention to behave disobedient effect on noncompliance of taxpayers.